Preparation and Characterization of Hierarchical Zeolite from Natural Zeolite Using Tandem Acid–Base Treatments - Indah Revita Saragi; Devi Yanti Christine (Journal of Technomaterial Physics, 2026)
Hierarchical zeolite was successfully synthesized from Lampung natural zeolite via sequential tandem acid–base treatments. The combined dealumination–desilication approach generated additional mesoporosity while preserving the zeolite's crystalline framework, as confirmed by X-ray diffraction (XRD). Nitrogen adsorption–desorption isotherms revealed a transformation from Type I to Type IV behavior, indicating successful mesoporous formation. The BET surface area increased from 4.795 to 16.855 m²/g, accompanied by a significant increase in mesopore volume. Elemental analysis showed that the Si/Al ratio decreased from 8.42 to 2.44 due to the dominant extraction of silicon during alkaline treatment. The modified zeolite (Zeolite-PTAB) exhibited enhanced Cu²⁺ adsorption capacity (19.3 mg/g) compared to raw zeolite (16.1 mg/g), with removal efficiency improving from 53.7% to 64.3%. These findings demonstrate that tandem acid–base treatment provides a simple and effective strategy for upgrading Indonesian natural zeolite into a hierarchical adsorbent for heavy-metal removal applications.